Non-equilibrium Quantum Simulations using Thimble Methods - Woodward, Simon (2023)
Our understanding of time dependent phenomena in particle physics is hampered by our inability to effectively investigate non-equilibrium phenomena, even using computers, due to the ‘Sign Problem’. This problem means that for nonperturbative theories, it is functionally impossible to evaluate Feynman path integrals to calculate the expectation values of operators. Here I present a possible remedy to this problem in the form of Generalised Thimble Techniques which, at great computational cost, suppress the Sign Problem and allow us to make headway in these investigations.